Students’ Learning Engagement in an Online Academic Listening and Speaking Class: Insights from a State University in Indonesia - Vindi Novita; Fuad Abdullah; Dewi Rosmala; Dea Silvani; Arini Nurul Hidayati (J-SHMIC : Journal of English for Academic, 2022)
The sudden shift of learning from traditional to online learning is worth noting once again. Students' learning engagement has always been a complicated thing to research but is worth mentioning and important for the educational department, especially in EFL countries. Students' learning engagement in online learning itself is an indicator in which students have in learning to achieve their goals. Empirically, there have been various studies of learning English listening and speaking and/or student engagement, however inadequate investigative attempts have concentrated on student engagement in academic listening and speaking skills, notably in the Indonesian higher education context and also in online learning. For this reason, the current study strives to delineate how students engage in the online learning of the Academic Listening and Speaking course. Besides, it also focuses on the factors affecting students' engagement in such an online course. With using thematic analysis, this qualitative study concluded that the students do engage in this online course as (1) cognitively engaged by understanding teaching materials and activities in the online ALS course, (2) emotionally engaged by enjoying classroom learning activities, and (3) behaviourally engaged by participating in a discussion, developing problem-solving skills, and applying online learning norms in the classroom. In addition, there are factors affecting students' engagement, including (1) social engagement of student and teacher rapport, (2) collaborative engagement of peer support, and (3) learning passions for Academic Listening and Speaking course.